Pelatihan Peningkatan Kemampuan Public Speaking melalui Pelatihan Master of Ceremony Bagi Himpunan Mahasiswa Jurusan - Jurusan Bahasa, Komunikasi dan Pariwisata (HMJ-BKP) - Enik Rukiati; Nodistya Septian Indrastana; Vigo Dewangga; Renata Kenanga Rinda; Yuslaili Ningsih (TAAWUN, 2024)
Public speaking is the skill of speaking in public using certain systems and rules, which are very important for every student. The service team created training aimed at improving public speaking skills among students majoring in language communication and tourism. The main focus of this training is the development of Master of Ceremony (MC) skills, which are considered a crucial aspect of communicating publicly. This activity aims to provide students with the skills needed to lead events, speak in public, and manage communications effectively. The training method involves a combination of theory and practical sessions by providing material in the field of public speaking and the Master of Ceremony and directing students to practice directly. The training participants consist of members of the Language, Communication, and Tourism Department Student Association who have an interest in honing their public speaking skills. During the training, they are taught presentation techniques, time management, good command of the language, and verbal communication. The evaluation results showed a significant increase in the participants' public speaking skills after attending the training. The participants not only experienced an increase in their confidence when speaking in public but were also able to handle situations that required language fluency and the ability to lead events.